Konseling Keluarga Struktural sebagai Salah Satu Pendekatan Konseling dalam Mengembalikan Peran dan Fungsi Anggota Keluarga - Ruzika Hafizha (Ma'soem University, 2022)
Family is the various units in society, where several people have roles and functions in the family system. Each family member is responsible for obeying and implementing each member and getting involved in problems so that an effective family is created. If there are family members who do not comply with these rules, the family structure will change both in terms of roles, experiences, and identities so that it will cause problems in the family. Problems that arise both from outside and from within the family itself can damage the family system. One effort that can be made to restore roles and functions in the family is through family guidance and counseling with a structural approach. The structural family counseling approach developed by Salvador Minuchin is an approach that can assist counselees in returning the functions and roles of family members to their original state by reorganizing family cohesion and improving relationships that occur within the family. The purpose of writing this article is to find out and obtain an overview of family counseling as a counseling approach in restoring the roles and functions of family members.